Evaluation of the Sensitivity Three of Immunological and Molecular Diagnostic Techniques for the Diagnosis of Toxoplasmosis in Women in Waist/ IRAQ - Jassim, Sura Emad (American Journal of Biology and Natural Sciences, 2025)
Background and objective: Toxoplasmosis is widely recognized as a highly widespread parasitic infection in humans, and is usually asymptomatic, capable of vertical transmission from mother to fetus. Clinical problems associated with toxoplasmosis during pregnancy include spontaneous miscarriage, stillbirth, and congenital form is one of the most important clinical aspects of this disease. This study aimed to determine the prevalence of toxoplasmosis in women infected with T. gondii in Waist Province, and to provide insight into the impact of the disease on reproductive health and determine anti-toxoplasma antibodies, and Toxoplasma DNA . Methods: One hundred and twelve women who were examined for laboratory testing were enrolled in this cross-sectional study. The prevalence of toxoplasmosis in women in Iraq may vary depending on factors such as geographic location, sample size, and diagnostic methods used Blood samples were tested for specific anti-toxoplasma IgM and IgG antibodies using an enzyme-linked immuno-sorbent assay (ELISA) and VIDAS TOXO IgG II Procedure and Confirm at detection of T. gondii by PCR. Results: Of 64 sera examined of female 14 (21.8 %) were seropositive for anti-toxoplasma IgG by Minividas TOXO IgG device . Using ELISA test, 25 (22.3%) of the sera examined were seropositive for anti-toxoplasma IgM. The ELISA test finding for anti-toxoplasma IgM the sera 4 sample only examined were subsequently subjected to PCR. Thus, PCR analysis for detecting T. gondii DNA in the blood of female was positive in 4 (16 %) of the DNA samples. Conclusion: The finding of this study indicates that ELISA and PCR is a more sensitive molecular techniques than a serological assay for the direct diagnosis of T. Gondii in the blood women.